Obscured by its omnipresence?: conceptual and practical issues around measuring alcohol-related crime in England and Wales - Lightowlers, Carly (The crime data handbook, 2024)
Alcohol is commonly associated with crime; while never a sole cause, alcohol consumption can be a salient contributory factor, influencing aetiology, nature, severity and harms inflicted. Its impact varies across crime types, and its association with violent crime is known to be stronger than with other forms. Crucially, the harms arising from alcohol-related crime can be significant, and accurately identifying and measuring such incidents is a crucial step in understanding and addressing this. Yet defining and measuring alcohol-related crime is riddled with a range of conceptual and practical issues. Practically, for example, it is widely accepted that police often fail to record the presence of alcohol in incidents they engage with – particularly where an alcogenic environment (for example, night-time economy spaces) obscures alcohol’s role through its omnipresence. Conceptually, establishing alcohol’s role in any given incident is necessarily a subjective interpretation, and as such can be contested, affecting its measurement in crime statistics. Exploring these practical and conceptual issues, this chapter suggests alcohol’s widespread involvement in violent crime in particular renders it mundane and intractable, and its extent likely underestimated. It also discusses how the measurement of alcohol-related crime – and the unresolved issues with this – affects responses to it. Considering victimization and perpetrator surveys, as well as police recorded crime statistics, this chapter also reflects on ways to improve measurement practices to better understand the extent and nature of alcohol-related crime.